Alloy selection for service in hydrogen fluoride, hydrofluoric acid and fluorine : a guide to the use of nickel-containing alloys - Dillon, C. P.; Davies, Michael, Dr (Nickel Institute, 2019)
This publication describes the behaviour of nickel-containing alloys and the specific nature of their reactivity with AHF and hydrofluoric acid, considered separately. The behaviour of other metals commonly used in the manufacture or handling of these chemicals is also discussed. Table 1 lists the main nickel-containing alloys and their UNS number considered in this introductory publication.
Keywords: Nickel alloys.; elektronické knihy; electronic books